THE EFFECT OF WORK DISCIPLINE AND TEAM WORK ON EMPLOYEE PERFORMANCE (CASE STUDY AT PT. BAHASA TECHNOLOGY SOLUTIONS) - Paoki, Esther Patricia; Saerang, David P.E; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Human resource is a critical factor that affects the performance of the employees. Without employees an organization or a company can not run their mission and also vision. To improve the employee performance in an organization, they should enforce discipline of the employees and also team work. This research aims to analyze the effect of work discipline and team work on employee performance at PT. Bahasa Technology Solutions. The type of this research is a quantitative research. Multiple Regression Analysis was used in this research. The population observed all the employees at PT. Bahasa Technology Solutions, so the sample of this research is the same as the population, which are 30 respondents. This research result shows that the independent variable work discipline has no significant effect on employee performance and team work has significant effect on employee performance.Â Keywords: Work Discipline, Team Work, Employee Performance, Multiple Linear RegressionÂ